Methodology For Integrating Educational Subjects Based On Electronic Devices Created In Engineering Education (Texas Journal of Engineering and Technology, 2023)
Knowledge of the principle of creation and operation of didactic electronic devices in the article presented the results of knowledge and practical experience obtained from teaching physics using the interdisciplinary integrated STEAM educational methodology.